A melancholic theatre: A study of two works by César De María - Paredes Morales, Judith Mavila (2022)
In this work, we try to study the metaphor and allegory of the disease proposed by the Peruvian playwright César De María. These tropes show the characters confronting each other in an unequal society from the body. In this way, De María’s proposal configures the corporeal from a marginal space, where the hegemonic logic can be decentered. Therefore, we formulate that theatrical works: ¡A ver, un aplauso! and Morir cantando trace a series of resistances: the disease and the pandemic. Following the approaches of Stefano Arduini on the figurative field of metaphor and Walter Benjamin on allegory, we will observe how these works, the first written and exhibited before the pandemic, already proposed the topic of illness to question a reality, that of others bodies, and the second staging in the midst of a pandemic, makes use of new technologies, and puts the topic of death on the table. In this way, the metaphor and the allegory acquire another vision of the world and feed the formation of another representation.